2018
DOI: 10.21037/jtd.2018.07.15
|View full text |Cite
|
Sign up to set email alerts
|

Management of broncholithiasis

Abstract: Broncholithiasis refers to the presence of calcified material that erodes into the lumen of the tracheobronchial tree or lung parenchyma, potentially causing inflammation and obstruction (1). Consequences from broncholithiasis range widely from being asymptomatic to life threatening such as recurrent pneumonias, hemoptysis, and bronchoesophageal fistula. Management varies depending upon several factors including patient symptoms, associated lung disease, and mobility of the broncholith within the airway, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Various bronchoscopic methods have been described for the removal of broncholiths. Forceps, laser photocoagulation, and cryoprobe extraction have all been shown to help in extracting broncholiths [4,14]. Laser-assisted broncholithotripsy has also been described for removing impacted broncholiths [15].…”
Section: Discussionmentioning
confidence: 99%
“…Various bronchoscopic methods have been described for the removal of broncholiths. Forceps, laser photocoagulation, and cryoprobe extraction have all been shown to help in extracting broncholiths [4,14]. Laser-assisted broncholithotripsy has also been described for removing impacted broncholiths [15].…”
Section: Discussionmentioning
confidence: 99%
“…The most common methods of treatment are therapeutic bronchoscopy and surgery. Most reports of therapeutic bronchoscopy indicate that broncholiths are treated as foreign bodies, removed using foreign body forceps, rigid forceps, or a Fogarty balloon catheter [3]. Jin et al [4] reported a treatment of intraluminal broncholith with a success rate of only 50%(2/4), Seventeen out of 19 patients with transluminal broncholiths received thoracotomy, only two patients received rigid bronchoscope.…”
Section: Introductionmentioning
confidence: 99%
“…1 The calcified substances are derived from chronic necrotizing granuloma infection including tuberculosis, histoplasmosis and rare actinomycosis, which cause calcification of mediastinal and hilar lymph nodes. 2 Broncholiths are classified into intraluminal, transluminal and extraluminal acc-ording to the anatomy between calculus and bronchial lumen confirmed by chest CT or bron-choscopy. An intraluminal broncholith means that the stone is confined to the bronchia lumen, while an extraluminal broncholith means that the stone is located outside the bronchial lumen and does not penetrate the bronchial wall.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the treatment methods of broncholithiasis mainly include bronchoscopy and surgical intervention. 2 Intraluminal broncholiths can be removed entirely or in part by biopsy forceps, foreign body forceps or net baskets under bronchoscope, with or without pretreatment of holmium laser lithotripsy. 6 Olson et al 7 have reported that intraluminal broncholiths can be removed by a rigid bronchoscope or flexible bronchoscope with a 100% success rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation